P63 expression profile in uterine cervical lesions - Qasim, Yusra Abdulkhaliq (Zanco Journal of Medical Sciences (ZJMS), 2020)
Background and objective: P63 is a member of the p53 gene family. It plays an essential role in the normal development of the cervix. This study aimed to assess p63 expression in different cervical lesions and the correlation between their expression in cervical intraepithelial neoplastic changes and invasive cervical cancer. Methods: A total of 62 cervical tissues were performed for p63 immunostaining, including 15 samples of non-neoplastic reactive cervicitis, 27 cervical intraepithelial neoplastic changes, and 15 invasive cervical cancer cases as well as five samples of normal cervical tissue as control. Results: P63 in normal cervical squamous epithelium had restricted staining pattern in the nuclei of basal cells. Reactive cervicitis staining ranged from restricted staining pattern in basal cells to mild increase in staining intensity involving upper parabasal cells. P63 was positive in all CIN lesions, and staining intensity increased significantly with increasing severity of cervical intraepithelial lesions compared with non-neoplastic epithelium. All cervical squamous cell carcinoma had high staining intensity while adenocarcinoma and small cell carcinoma were stained negative. Conclusion: P63 can be used as a marker for the distinction between reactive cervicitis and cervical intraepithelial changes. It is also of value for grading of CIN lesions and differentiation between squamous cell carcinoma, adenocarcinoma, and small cell carcinoma.